Migration as A Catalyst for Socio-Economic Development in Ghana: A Transformationalist Perspective - Amoako, Ester; Adjei, Yaw Agyeman; Nyarko, Kwaku Owusu (Baileo: Jurnal Sosial Humaniora, 2025)
This article examines the role of migration as a catalyst for socio-economic development in Ghana through a transformationalist approach to social change. The primary objective of this study is to explore how the dynamics of social transformation influence and are influenced by migration, with a focus on the bidirectional relationship between the two. Employing a mixed-methods approach, the study integrates both qualitative and quantitative analyses and applies a transformationalist theoretical framework to understand the processes of social change that have unfolded in Ghana over the past decade. The findings reveal that while a reciprocal relationship between migration and social transformation is widely perceived, the influence of social transformation on migration patterns and flows is significantly more pronounced. Regressive changes were recorded in the economic domain, whereas technological and demographic aspects experienced considerable progress. In contrast, political and cultural dimensions have remained relatively stagnant. Notably, exceptions to this directional influence are found in the areas of higher educational attainment and improved household income—both of which are directly stimulated by migration experiences. These findings offer new insights into migration not merely as a consequence of social transformation, but also as a selective driver of specific forms of change. The article recommends the adoption of a cross-sectoral approach in socio-economic development policies, positioning migration as a strategic variable in social planning and the advancement of social sciences and humanities, particularly within the context of developing countries such as Ghana.